Increasing soybean productivity by plant equidistant arrangements and modification of technology levels of cropping systems - Silva, Rodrigo Rocha; Macedo, Willian Rodrigues (Revista de Ciências Agroveterinárias, 2022)
The arrangement of soybean plants defines their ability to recognize the environment and improve their abiotic and biotic interactions with it. This study aimed to evaluate the effect of planting arrangements associated to two distinct crop systems (high technological level or conventional crop level) for the soybean varieties 8473 RSF and AS 3730, to evaluate the plant performance and productivity in the field. A double factorial scheme was used with two varieties and six spatial arrangements. Two experiments were conducted during the 2017–2018 crop season: the first was based on standard cultivation of the Brazilian Cerrado (without irrigation systems and adequate fertilizer), whereas the second utilized high technology (irrigation systems and increased fertilizer). The morphophysiological parameters, normalized difference vegetation index (NDVI), leaf pigment content and crop yield parameters were evaluated. Our study pointed out the positive responses for both cultivated varieties and two technological levels adopted cultivated under equidistant arrangement and high density. The leaf area index, leaf pigment content, NDVI, and crop production showed substantial responses under different equidistant arrangements. Therefore, this procedure requires adjustments in the level of cultivation technology and identification of the most suitable soybean variety.